The Story of My Boyhood and Youth - Muir, John, 1838-1914 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Story of My Boyhood and Youth" by John Muir is an autobiographical memoir written in the early 20th century. The narrative recounts Muir's early experiences growing up in Scotland, focusing on his deep affinity with nature and adventure. It offers a vivid exploration of his childhood, emphasizing his wild pursuits, education, and the formative moments that shaped his love for the natural world. The opening of the memoir delves into Muir's early life in Dunbar, Scotland, where he shares vivid recollections of his explorations with friends and the thrill of discovering the wild surroundings. Muir reminisces about his school days filled with frightful legends, such as the "Dandy Doctor," and the joys of simple childhood games and adventures in nature. Through charming anecdotes and reflective observations, he sketches a portrait of a spirited boy whose experiences in the fields and by the sea began to cultivate a lasting passion for the environment that would characterize his later life as a naturalist and conservationist. (This is an automatically generated summary.)
Release date is 2006-05-09
Juliet Sutherland, Jeannie Howse and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Naturalists -- United States -- Biography; Conservationists -- United States -- Biography; Muir, John, 1838-1914 -- Childhood and youth; Frontier and pioneer life -- Wisconsin; Wisconsin -- Social life and customs